THE f1J11JRE OF WORK: THOUGHTS ABOUT EMERGING CHANGES IN THE ENVlRONMENTAL WORKPLACE ANO ITS IMPACT ON THE TRAINING ANO KNOWLEOGE IN ADVANCED SOCIETIES - Bas, Enric; Guillo, Mario (Cuadernos de Administración, 2008)
The globa l context and changing in which organizations currently operate (publÍc or private), expect that they approach the different probJematic be faced from a holistic perspective and in advance. One ofthe key Íssues that arise are the changes that are taking place in the level global - and with more strong inside the advance societies -in the organization of work, changes faster and whose main characteristic of the dissolution traditional models ofproduction and organization. We are faced wÍth what Zygmunt Bauman called "liquÍd society", a historical period marked by instability and social defenseless and where the management of complexity and changes uppose a challenge for trying to anticipate which are going to be the characteristics of new mode ls of organizations structures, models of models from whÍch theÍr needs in the subject fo r human re sources.